MRI Imaging, Comparison of MRI with other Modalities, Noise in MRI Images and Machine Learning Techniques for Noise Removal : A Review - Sajid Ullah, Khan; Najeeb Ullah, Khan; Irshad, Ahmed; Wang, Yin Chai (Bentham Science Publishers, 2019)
Medical imaging is to assume greater and greater significance in efficient and precise diagnosis process. It is a set of various methodologies which are used to capture internal or external images of human body and organs for clinical and diagnosis needs to examine human form for various kind of ailments [1]. Computationally intelligent machine learning techniques and their application in medical imaging can play a significant role in expediting the diagnosis process and making it more precise. This review presents an up-to-date coverage about research topics which include recent literature in the areas of MRI imaging, comparison with other modalities, noise in MRI and machine learning techniques to remove the noise.